Peripheral Oxidative Stress Biomarkers in Spinocerebellar Ataxia Type 3/Machado–Joseph Disease - de Assis, Adriano M.; Saute, Jonas Alex Morales; Longoni, Aline; Haas, Clarissa Branco; Torrez, Vitor Rocco; Brochier, Andressa Wigner; Souza, Gabriele Nunes; Furtado, Gabriel Vasata; Gheno, Tailise Conte; Russo, Aline; Monte, Thais Lampert; Castilhos, Raphael Machado; et al. (Frontiers in Neurology, 2017)
Objectives: Spinocerebellar ataxia type 3/Machado-Joseph disease (SCA3/MJD) is a polyglutamine disorder with no current disease-modifying treatment. Conformational changes of mutant ataxin-3 trigger different pathogenic cascades, including reactive oxygen species (ROS) generation; however, the clinical relevance of oxidative stress elements as peripheral biomarkers of SCA3/MJD remains unknown. We aimed to evaluate ROS production and antioxidant defense capacity in symptomatic and presymptomatic SCA3/MJD individuals and correlate these markers with clinical and molecular data with the goal of assessing their properties as disease biomarkers. Methods: Molecularly confirmed SCA3/MJD carriers and controls were included in an exploratory case-control study. Serum ROS, measured by 2′, 7′-dichlorofluorescein (DCFH-DA) as well as superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) antioxidant enzyme activities, levels were assessed. Results: Fifty-eight early/moderate stage symptomatic SCA3/MJD, 12 presymptomatic SCA3/MJD, and 47 control individuals were assessed. The DCFH-DA levels in the symptomatic group were 152.82 nmol/mg of protein (95% confidence interval (CI), 82.57 to 223.08, p<0.001) higher than in the control and 243.80 nmol/mg of protein (95% CI, 130.64 to 356.96, p<0.001) higher than in the presymptomatic group. The SOD activity in the symptomatic group was 3 U/mg of protein (95% CI, 0.015 to 6.00, p=0.048) lower than in the presymptomatic group. The GSH-Px activity in the symptomatic group was 13.96 U/mg of protein (95% CI, 5.90 to 22.03, p<0.001) lower than in the control group and 20.52 U/mg of protein (95% CI, 6.79 to 34.24, p<0.001) lower than in the presymptomatic group and was inversely correlated with the neurological examination score for spinocerebellar ataxias (R=-0.309, p=0.049). Conclusions: Early/moderate stage SCA3/MJD patients presented a decreased antioxidant capacity and increased ROS generation. GSH-Px activity was the most promising oxidative stress disease biomarker in SCA3/MJD. Further longitudinal studies are necessary to identify both the roles of redox parameters in SCA3/MJD pathophysiology and as surrogate outcomes for clinical trials.